Accuracy of reported family histories of essential tremor - (:unkn) unknown (LITTLE BROWN CO, 1996)
We studied the accuracy of reported family histories of essential tremor (ET) by questioning the patients in our clinic and subsequently by mail and phone. For individuals who continued to report a negative family history, we mailed a screening questionnaire to their first-degree relatives to further ascertain the presence of ET. On initial assessment, 67.7% of patients reported a positive family history of ET, but following all assessments, 96.0% of patients had a positive family history. We conclude that a negative family history of ET is often inaccurate, and that ET is primarily a hereditary disease.